THE IMPACT OF PERSONAL DATA ON MONGOLIA’S NATIONAL SECURITY - Munkhjargal Bayanjargal; Munkhtsetseg Erdenebulgan; Densmaa Batbayar (International Journal of Innovative Technologies in Social Science, 2025)
Personal data is not only a matter of citizen privacy but also a crucial resource for national security strategy and a fundamental requirement for ensuring state information security. This study explores the theoretical and practical implications of personal data breaches on Mongolia’s national security, state secrecy, and the stability of its electronic infrastructure, drawing on international and domestic experiences. The research examines the enforcement of existing laws and policy documents in Mongolia and analyzes cases of data breaches in information systems critical for national security. A comparison is made between the legal and institutional frameworks for data protection in countries like the European Union, the United States, and Japan. The study highlights the importance of enhancing information security education in Mongolia, fortifying the national electronic infrastructure, and proposing enhancements to the legal framework for safeguarding personal data.